Epidemiology of interpersonal violence at a regional hospital emergency unit in the Eastern Cape, South Africa - Amitabh Mitra; Uchenna B. Okafor; Ramprakash Kaswa; Oladele V. Adeniyi (South African Family Practice)
Background: This study describes the profile, mechanism and pattern of injuries, and highlights important gaps in clinicians’ consultations with patients who experienced interpersonal violence (IPV) in the predominantly black South African township of Mdantsane, Eastern Cape.